Motivational Interview as a Method of Treating People with Dual Diagnosis - Lipczyński, Andrzej; Kinal, Jarosław (European Scientific Journal, ESJ, 2018)
The ideal, the spiritual and the most important element of motivational intelligence is cooperation. The idea is to focus on helping with motivational problems where the customer is not ready or willing to change or have a sense of ambivalence. It is certain that motivational intelligence is not a collection of techniques. This involves the attitude of the therapist, who does not assume absolute authoritarian attitude and is more of a partner, and rather is to investigate the client’s problems with the exclusion of the attitude of giving instruction, moralistic recommendations. It is generally about support and more about creating a friendly interpersonal atmosphere that encourages cooperation. The therapist’s tone of wisdom is not acceptable, but rather the actual picture of the condition being extracted from the patient. This method is more like Socrates than university lecturer. The form of educare, mining is the most appropriate. The goal is to discover within yourself the motivation for change and its extraction. The article describes the motivational intelligence technique as a tool for social workers.